Functional properties of electrolytic alloys of Cobalt with Molybdenum and Zirconium - Ved', M.V.; Koziar, M.A.; Sakhnenko, N.D.; Slavkova, M.A. (Functional Materials, 2016)
Functional electrolytic alloy coatings of Co-Mo and Co-Mo-Zr were deposited on substrates of 3 type steel from polyligand citrate-pyrophosphate bath using pulsed current. It is shown the alloying components content, their distribution on the surface, morphology and topography of the coatings are depended on the electrolysis energetic parameters. It is confirmed that the functional properties of the binary and ternary electrolytic cobalt alloys (corrosion resistance, catalytic activity both in hydrogen evolution and carbon II oxide oxidation) are predetermined by material composition, morphology and surface relief. Chemical stability of Co-Mo, and Co-Mo-Zr systems in aggressive media is conditional on increased susceptibility to passivity when the molybdenum and zirconium are incorporated in the coating, and the stability is a prerequisite of their use for corrosion protection. The high level of catalytic properties of Co-Mo, and Co-Mo-Zr coatings associated with different affinities for alloying metals to oxygen as well as verification of hydrogen evolution mechanism allows to recommend them for platinum metals replacement in the heterogeneous catalysis.